RIGHTS, DEMOCRACY AND DEVELOPMENT: THE JUDICIAL SYSTEM’S ROLE IN DEVELOPING COUNTRIES - Ferreira, Vivian Maria Pereira; Langenegger, Natalia (PANORAMA OF BRAZILIAN LAW, 2015)
This article seeks to discuss whether and how the judicial system has been assuming a new institutional role in the design of public policies aimed at promoting of Economical Social and Cultural Rights (ESCR) in developing countries. Considering that these rights are crucial for human and social development, the article discusses the ways in which the judicial system might interfere with the process of development.Alongside a theoretical debate, the article presents a functionalist comparative study of the public interest litigation in Brazil, India and South Africa. It focuses on how judges seek to promote ESCR as well as on the benefits and problems of their intervention in public policies created by democratic governments and legislatures.The diagnosis that judicial systems around the world play different roles from the ones recommended by the economic neoliberal mainstream shows that several different institutional arrangements are possible and that some of them might be more adequate to the reality of the developing world. Therefore, the article hopes to provide insights to rethink global governance and the current knowledge on law and political economy from a new paradigm.